ON THE CANCER FRONTIER : ONE MAN, ONE DISEASE, ABD A MEDICAL REVOLUTION - Marks, Paul A., (PUBLICAFFAIRS, 2014)
"Paul Marks M.D., President Emeritus of Memorial Sloan-Kettering Cancer Hospital, attributes the elusive nature of cancer's cure to its inherently anarchic processes. In 1950, the discovery of cancer was all but a death sentence. By 1980, 214 of every 100,000 Americans died from cancer. As late as 1986, an article in the New England Journal of Medicine revealed the less-than-optimistic outlook cancer research, publishing the condemning sentence: "We are losing the war against cancer." In fact, though cancer had not been eliminated, it had begun to be identified for what it is. A highly individualistic disease, variable-a guerrilla cell rather than a marching army. Suddenly science learned how to fight the right war-at ever closer quarters. And at the forefront of the momentous chain of discoveries was Paul Marks. Chronicling the insights of researchers and doctors around the world and the momentous effects of their pains-taking advances- Marks weaves together the humbling account of how and what we learned about the mechanisms of malignant and abnormal cells that make up every one of us"--Provided by publisher.